Deconstructing Genius A Conversation with Darrin Mcmahon. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and intellectual historian Darrin McMahon, Dartmouth College. The word ""genius"" evokes great figures like Einstein, Leonardo Da Vinci, and Mozart but what quintessential quality unites these individuals? Can we measure it? Can we create it? This thoughtful conversation explores Darrin McMahon's research on the evolution of genius from Plato to Einstein (which led him to write the book Divine Fury: A History of Genius) in an effort to illuminate what our evolving genius mythology reveals about the rest of us. This car.